Derek Jarman's Angelic Conversations - Ellis, Jim, 1964- (Book collections on Project MUSE., 2009)
Best known as an iconoclastic, wildly inventive filmmaker, Derek Jarman was also an accomplished author, painter, and landscape artist. In Derek Jarman's Angelic Conversations, Jim Ellis considers Jarman's wide-ranging oeuvre to present a broad perspective on the career and life of one of the most provocative, engaged, and important artists of the twentieth century.